Mutations in the E1 Hydrophobic Domain of Rubella Virus Impair Virus Infectivity but Not Virus Assembly - Qiu, Zhiyong (American Society for Microbiology, 2000)
Rubella virus (RV) virions contain three structural proteins, a capsid protein that interacts with viral genomic RNA to form a nucleocapsid and two membrane glycoproteins, E2 and E1. We found that substitution of either an aspartic acid residue at Gly93 (G93D) or a glycine residue at Pro104 (P104G) in the internal hydrophobic domain of E1 affected virus infectivity but not virus assembly. Viruses carrying G93D and P104G mutations had impaired infectivity, reduced 1,000-fold and 10-fold, respectively. A revertant was isolated from the G93D mutant. Sequencing analysis showed that the substituted aspartic acid residue in G93D mutant had reverted to the original glycine residue, suggesting the involvement of Gly93 in membrane fusion during viral entry.